Examining the relationship between rightward visuo-spatial bias and poor attention within the normal child population using a brief screening task. - Manly, Tom; Cornish, Kim; Grant, Cathy (Journal of Child Psychology & Psychiatry & Allied Disciplines., 2005)
Background: Some previous studies have linked Attention Deficit Hyperactivity Disorder (ADHD) with a bias in spatial awareness away from the left. As genetic research suggests that ADHD may be better viewed as an extreme on a continuum rather than a distinct entity, here we examined this issue in boys from the normal population. Method: From an initial sample of 1811, two groups of boys characterised by very high (n = 58) or very low (n = 68) levels of ADHD-type behaviours were formed. The groups completed the spatially sensitive Line Bisection test and more general measures of (non-spatial) attention and intellectual function. Results: Boys whose bisections were consistent with relative inattention to the left indeed had higher ratings of ADHD-type behaviours and performed significantly more poorly on tests of sustained attention and executive function than boys whose bisections were in the normal range. In contrast, boys who showed extreme bisections in the opposite direction were not unusual either in ratings or test performance. Conclusions: The results support an association between poor attention and a relative rightward bias in visual awareness that may stem from right hemisphere inefficiency. Reprinted by permission of the publisher.